Spectral properties of Sturm-Liouville equations with singular energy-dependent potentials - Pronska, N. (Methods of Functional Analysis and Topology, 2013)
We study spectral properties of energy-dependent Sturm–Liouville equations, introduce the notion of norming constants and establish their interrelation with the spectra. One of the main tools is the linearization of the problem in a suitable Pontryagin space.